Plasma generator: design of six stage cockcroft-walton voltage multiplier 12 kV for impulse voltage generation - Wijono Wijono; Eka Maulana; Dony Darmawan Putra; Waru Djuriatno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Cockcroft-Walton (CW) voltage multiplier is a voltage booster circuit with an array of series-connected only diodes and capacitors. In this research, voltage multiplier is designed to generate voltage up to 12 kV that the modified 6-stage constructed generator. It is designed as circuit charger of storage capacitor (CS) to generate combination wave impulse application which following standard those set in IEC (International Electrotecnical Commission) 61000-4-5 class 4. CS should be charged up to 4 kV according this standard. High impulse voltage and current works repeatedly in a short time, so the charging system is expected to reach targeted voltage within a maximum time of 10 seconds. Besides charging is also required to design of circuit discharger for discharging electric charge inside the CS. It is expected to reach 0 kV within a maximum time of 15 seconds with overdamped technique. There are three results of the research projects such as output voltage of CW voltage multiplier before connecting CS, charging time of CS, and discharging time of CS. The result showed that CW voltage multiplier can generate up to 12.01 kV on simulation and 11.9 kV on experiment. CS can be charged up to 4 kV in 9.8 seconds on simulation and 7.9 seconds on experiment. CS can be discharged in 14.2 seconds on simulation and 10 seconds on experiment. These results are in accordance with the expectation.